Comparison between Fuzzy Logic Controller (FLC) and Fractional Order Proportional Integral Derivative (FOPID) Controller on Water Level and Steam Temperature of Steam Drum Boiler - Zainullah Zuhri; Mardlijah Mardlijah; Didik Khusnul Arif ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2018)
Steam drum boiler is an important component of boiler on electric steam power plant which is useful to obtain steam. The obtained steam makes turbine spin. In order to obtain maximal result for the steam power plant (PLTU) 1-2 PT PJB UP Gresik, the water level of steam drum boiler must be 0.7625 m and the temperature of steam drum boiler must be 786 K. Thus, it needs some controller to keep the position of water level and the temperature stable. In this problem, we compare two controllers FLC and FOPID. It can be concluded that FLC works better than FOPID controller. Nevertheless, FOPID controller has faster response time than FLC, i.e. no overshoot and more robust when disturbance is present on the system.